1999
DOI: 10.1093/ajcp/111.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Features Associated with Lymph Node Metastasis in Stage T1 and Superficial T2 Rectal Adenocarcinomas in Abdominoperineal Resection Specimens: Identifying a Subset of Patients for Whom Treatment with Adjuvant Therapy or Completion Abdominoperineal Resection should be Considered After Local Excision

Abstract: llmage 21 Grade 3 (poorly differentiated) adenocarcinoma.The neoplasm is formed by complex, irregular, cribriform glands and small solid areas (H&E, x76.8).5 2 Am J Clin Pathol 1999;111:51-58

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
2
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 21 publications
2
65
2
2
Order By: Relevance
“…Our results are concordant with the results of Morodomi et al, Goldstein et al, and Okuyama et al, who reported that tumor budding is associated with pathological parameters including venous invasion and lymph node metastasis in colorectal carcinomas (10,18,19). These findings support the idea that tumor buds originate from the cells which have higher malignant potential.…”
Section: Resultssupporting
confidence: 93%
“…Our results are concordant with the results of Morodomi et al, Goldstein et al, and Okuyama et al, who reported that tumor budding is associated with pathological parameters including venous invasion and lymph node metastasis in colorectal carcinomas (10,18,19). These findings support the idea that tumor buds originate from the cells which have higher malignant potential.…”
Section: Resultssupporting
confidence: 93%
“…Hase et al (1993) reported that tumour budding was an important predictor for recurrence and poor prognosis in patients with colorectal cancers. Furthermore, some oncologists and pathologists showed that tumour budding was significantly associated with lymph node metastasis, local recurrence, distant metastasis and poor prognosis in advanced colorectal cancers (Ono et al, 1996;Goldstein and Hart, 1999;Okuyama et al, 2002;Ueno et al, 2002). In previous reports, tumour budding was detected by using H.E specimens.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is difficult to identify a lymphatic involvement by cancer cells with routine haematoxylin and eosin (H.E) staining and both the sensitivity and the positive predictive value of this risk factor for lymph node metastasis remain low. Studies of advanced colorectal cancers have recently demonstrated that tumour budding at the invasive margin is a risk factor for lymph node metastasis (Morodomi et al, 1989;Hase et al, 1993;Ono et al, 1996;Goldstein and Hart, 1999;Okuyama et al, 2002;Ueno et al, 2002;Tanaka et al, 2003;Park et al, 2005). However, so far there have been few studies that have examined tumour budding in submucosal carcinomas with respect to lymph node metastasis (Makino et al, 2000;Masaki et al, 2001b;Ueno et al, 2004).…”
mentioning
confidence: 99%
“…Among the suggested grading schemes, both the number of strata, as well as the criteria for distinguishing among them, vary markedly. In some systems, grade is defined on the basis of a single microscopic feature, such as the degree of gland formation, and in other systems, a large number of features are included in the evaluation (14). Irrespective of the complexity of the criteria, however, most systems stratify tumors into three or four grades as follows:…”
Section: Sporadic Colorectal Cancer: the Basics That Are Not So Basicmentioning
confidence: 99%